The Relevance of Philosophy and Sufism from the Perspective of Sheikh Abdul Halim Mahmud - Fauzi, M. Ihsan (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
This article examines the views of Shaykh Abdul Halim Mahmud on the relationship between philosophy and Sufism in the context of ma‘rifatullah (knowledge of God). The purpose of this study is to demonstrate that philosophy and Sufism are not conflicting disciplines, but rather complementary paths toward the perfection of ma‘rifatullah. This research employs a qualitative approach using a literature review of the works of Shaykh Abdul Halim Mahmud and classical Islamic philosophical sources. The study finds that philosophy is understood as ḥikmah or rational effort to know God through the medium of reason, while Sufism pursues the path of taṣfiyah (purification of the soul) to attain a higher level of divine knowledge. Shaykh Abdul Halim Mahmud asserts that reason alone is insufficient to achieve perfect ma‘rifatullah without being complemented by inner purification. This view aligns with Plotinus’s concept of the stages of “finding God” through reasoning and “connecting with God” through spiritual purification, as well as the philosophical illustration found in Ibn Ṭufayl’s Hayy Ibn Yaqzan. The study concludes that the integration of philosophy and Sufism represents a comprehensive intellectual and spiritual approach to drawing closer to God and understanding reality in depth.